The Relation of Micro-segmentation, Customer Experience, Customer Satisfaction and Its Effect on Brand Trust in C2C E-Marketplaces - Castillo-Sotomayor, Sandra (2023)
The objective of this study is to understand the effects of micro-segmentation, customer experience and customer satisfaction on overall brand trust. Moreover, the main contributions of this study are based on the evaluation of these variables within the consumer-to-consumer (C2C) dynamic. The research was performed on a sample of people that actively purchase via C2C e-marketplaces, and the results of the survey were examined by the PLS-SEM analysis. It was identified a positive effect of micro-segmentation toward customer experience, also it proved that a correct customer experience leads to customer satisfaction and lastly, brand trust is achieved by the positive effect from customer experience and satisfaction. The analysis has supported most of the hypothesized relationships.